Highly Efficient Oxygen Evolution Reaction Enabled by Phosphorus Doping of the Fe Electronic Structure in Iron–Nickel Selenide Nanosheets. Issue 18 (24th July 2021) - Huang, Yuan; Jiang, Li‐Wen; Shi, Bu‐Yan; Ryan, Kevin M.; Wang, Jian‐Jun
Abstract: The electronic structure of active sites is critically important for electrochemical reactions. Here, the authors report a facile approach to independently regulate the electronic structure of Fe in Ni0.75 Fe0.25 Se2 by P doping. The resulting electrode exhibits superior catalytic performance for the oxygen evolution reaction (OER) showing a low overpotential (238 mV at 100 mA cm −2, 185 mV at 10 mA cm −2 ) and an impressive durability in an alkaline medium. Additionally, the mass activity of 328.19 A g −1 and turnover frequency (TOF) of 0.18 s −1 at an overpotential of 500 mV are obtained for P─Ni0.75 Fe0.25 Se2 which is much higher than that of Ni0.75 Fe0.25 Se2 and RuO2 . This work presents a new strategy for the rational design of efficient electrocatalysts for OER. Abstract : The precise electronic structure regulation of Fe in Ni0.75 Fe0.25 Se2 by P doping leads to the P─Ni0.75 Fe0.25 Se2 electrode with remarkable electrocatalytic activity and stability for oxygen evolution reaction (OER).